2005
DOI: 10.1021/ja043218k
|View full text |Cite
|
Sign up to set email alerts
|

A Metastable Prerequisite for the Growth of Lumazine Synthase Crystals

Abstract: Dense liquid phases, metastable with respect to a solid phase, form in solutions of proteins and small-molecule materials. They have been shown to serve as a prerequisite for the nucleation of crystals and other ordered solid phases. Here, using crystals of the protein lumazine synthase from Bacillus subtilis, which grow by the generation and spreading of layers, we demonstrate that within a range of supersaturations the only mechanism of generation of growth layers involves the association of submicrometer-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
193
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(207 citation statements)
references
References 51 publications
12
193
2
Order By: Relevance
“…At the lowest temperature, the barriers encountered along the non-classical path are even lower so the advantage of this path is even greater. This picture agrees well with that developed by Vekilov and co-workers who have observed, by means of dynamic light-scattering, the presence of short-lived dense liquid droplets in protein solutions [6]. The results for the LJ system, shown in Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…At the lowest temperature, the barriers encountered along the non-classical path are even lower so the advantage of this path is even greater. This picture agrees well with that developed by Vekilov and co-workers who have observed, by means of dynamic light-scattering, the presence of short-lived dense liquid droplets in protein solutions [6]. The results for the LJ system, shown in Fig.…”
supporting
confidence: 92%
“…More recently, the simple picture has also been challenged by novel experimental investigations. Vekilov and co-workers have shown that, prior to crystallization, protein solutions harbor metastable droplets of dense fluid and they have suggested that these droplets are necessary precursors of crystallization [4,5,6,7]. The picture that emerges is one of the formation of metastable droplets of dense fluid which then subsequently crystallize.…”
mentioning
confidence: 99%
“…Two different models have been postulated to account for the quasi-instantaneous formation of multilayer stacks: the microcrystal-sedimentation scenario (28,33) and the cluster-assimilation scenario (34,35). In brief, the former model assumes coincidental sedimentation of freshly bulk-nucleated microcrystals in an at-random orientation onto the macrocrystal, followed by a rapid reorientation to align with the underlying lattice leading to a flawless merging of both phases (36).…”
Section: Resultsmentioning
confidence: 99%
“…The 2D clusters might be ordered or disordered, akin to a 2D liquid formed in the pool of hexamers adsorbed on the terraces: examples of liquid phases in 2D systems (50) have been discussed (51). A 3D analog of this process would be layer generation by the landing of dense liquid droplets on the surface of an existing crystal (52). In further analogy, the stacks of layers formed by 3D nucleation do not grow in height but expand laterally (52), a behavior similar to that of the mounds described above.…”
Section: The Mechanism Of Mound Formation: 2d Clusters On the Terracesmentioning
confidence: 99%